What emotions are elicited by smells in Japanese people? Emotional measurement using a universal scale in Japanese - Hirotada Hirama; Takahiro Miura; Shusuke Kanazawa; Yumeko Imamura; Shinya Kano; Tatsu Kobayakawa (PLoS ONE, 2025)
Odors can elicit emotions, and cultural differences exist in the emotions elicited. To enable cross-cultural comparisons, the Universal Emotion and Odor Scales (EOS), a psychological scale consisting of affective terms in multiple languages, has been developed and used to measure emotions. However, it does not include the Japanese language. In addition, similar surveys only examined the pleasantness or unpleasantness of odors among Japanese people. No studies examined their relationship with specific emotions. We created a Japanese version of the EOS (the Japanese version of the Geneva Emotion and Odor Scale; J-GEOS), which could be compared across cultures. In addition, we conducted an experiment to examine the relationship between odors and emotions among Japanese participants. The J-GEOS was created by translating the existing multilingual EOS into Japanese. It was also used to examine emotional attraction to 10 odors in 200 participants, which included older adults. This study showed that the J-GEOS could be used to describe emotions elicited by odors via further specific affective terms. We expect that the J-GEOS could be widely used as a comparative tool between various cultures to understand the psychological characteristics of olfaction among the Japanese.